Armillariella tabescens methanol extract ameliorates ulcerative colitis via inhibiting TLR4/NF-κB and NLRP3 activation and mediating intestinal barrier integrity. (December 2022) - Zhang, Wen-Na; Li, Yuan-Yuan; Xu, Jia-Jia; Shi, Lu-Lu; Chen, Lei; Lu, Yong-Ming; Wu, Qing-Xi; Luo, Jian-Guang; Chen, Yan
Graphical abstract: Highlights: Armillariella tabescens methanol extract (AME) significantly attenuated UC symptoms, suppressed the activity of myeloperoxidase (MPO), decreased the levels of LPS, TNF- α, IL-1 β, IL-18, and increased the level of IL-10 in serum. AME could improve the expression of tight junction proteins ZO-1, occludin and claudin-1. AME could inhibit the activation of TLR4/NF-κB and NLRP3 signaling pathways in colon tissue. Abstract: Armillariella tabescens is a traditional Chinese medicinal and edible fungus which holds importance for treatment of gastrointestinal disorders. This study was aimed to evaluate the effect of methanol extract of A. tabescens (AME) in dextran sulfate sodium (DSS) induced ulcerative colitis (UC). The results showed that AME significantly attenuated UC symptoms, suppressed the activity of myeloperoxidase (MPO), decreased the levels of LPS, TNF- α, IL-1 β, IL-18, and increased the level of IL-10 in serum. Besides, AME could improve the expression of tight junction proteins ZO-1, occludin and claudin-1. Moreover, AME inhibited the activation of TLR4/NF-κB and NLRP3 signaling pathways in colon tissue. In addition, eight compounds were identification in AME by high performance liquid chromatography (HPLC)-high resolution mass spectroscopy (HRMS). Therefore, this study indicated that AME was potential to be further developed into a suitable functional food additive or promising therapeutic agent for UC treatment.